Ligand and hard base assisted preparation of AgInS2 single phase nanocrystals for enhancing the photocatalytic activity of TiO2. (1st July 2021) - Yang, Min; Yan, Yujia; Liu, Enzhou; Fan, Jun; Hu, Xiaoyun
Abstract: As a typical sulfide bimetallic semiconductor material, AgInS2 has been widely studied for its excellent photoelectrochemical properties. However, due to the large lattice mismatch, it is difficult to obtain AgInS2 single phase nanocrystals by conventional reaction. Therefore, the ligand and pH were selected and adjusted for the preparation of AgInS2 single phase nanocrystals. Adding organic molecules containing sulfhydryl groups as ligands could combine with metal ions to form covalent bonds, while OH − could react with transition metal ions to form soluble metal hydroxides, which could protect metal ions from direct reaction with S 2− . With the help of x-ray powder diffraction, AgInS2 single phase nanocrystals were successfully prepared by hydrothermal reaction at 180 °C with L-cysteine (L-Cys) or glutathione as the ligand in an alkaline environment. Finally, it was determined that the AgInS2 single phase nanocrystals obtained when the ligand was L-Cys and the reaction time was locked to 24 h had high catalytic activity as determined by a rhodamine B (RhB) removal experiment. In addition, AgInS2 /TiO2 (AIS-TO) heterojunction photocatalysts were prepared by an in-situ hydrothermal method to improve the photocatalytic activity of TiO2 . Among them, the 5% AIS-TO sample showed the highest catalytic activity, and the degradation rate of RhB was 2.4 times that of TiO2 . It was also proved that electrons were transported by a Z-type mechanism in the AIS-TO heterojunction photocatalytic system. This work would provide a feasible scheme for the preparation of more sulfide bimetallic semiconductor single phase nanocrystals.